Potential impact factors on the enhancement of antibiotic resistance in a lake environment. (30th May 2022) - Sorn, S.; Sulfikar,; Lin, M-Y.; Shuto, M.; Noguchi, M.; Honda, R.; Yamamoto-Ikemoto, R.; Watanabe, T.
Abstract: There is considerable concern regarding antibiotic resistance in the water environment due to antibiotic residues from anthropogenic origins. The low antibiotic concentration in the water environment may promote the selection of antibiotic resistance. However, it is unclear how environmental factors affect resistance selection. We investigated the proliferation of quinolone-susceptible faecal bacteria ( E. coli ) exposed to low norfloxacin concentration (ng/L) at variable temperatures, exposure times, and carbon concentrations, simulating the conditions of the water environment. The induction of antibiotic resistance in thirteen E. coli isolates was more likely to occur at 37 °C. However, resistance also occurred at temperatures as low as 25 °C, provided a longer exposure time of 5 days. These results suggest that antibiotic resistance is more likely to be induced in regions where temperatures may reach 25–37 °C, such as tropical regions. HIGHLIGHTS: Increase MIC was different in E. coli isolates to exposure conditions. Higher temperature enhances resistance in more isolates. Longer exposure time increases higher resistance level. Low carbon conditions could develop bacterial resistance at a warm temperature of 25 °C. Graphical Abstract